The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.35848/1347-4065/acb6a1
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectroscopic measurement of time-varying ion composition in a pulse-modulated Ar/C4F8/O2 dual-frequency capacitively coupled plasma

Abstract: The time dependence of the ion composition in pulse-modulated dual-frequency capacitively coupled plasma with Ar/C4F8/O2 was measured using a quadrupole mass spectrometer with an electrostatic energy analyzer. After turning on the pulse, Ar+ ions were preferentially generated, and then, the composition of CxFy + ions, such as C2F4 + and C3F5 + ions, increased. This phenomenon was discussed on the basis of the time variation of electron temperature and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Signal time delay due to ion transit time through the QMS was considered. Our previous study 12) has confirmed the proportional relationship between the square root of ion mass number and the ion transit time, from light ions (CF + ) to heavy ions (C 3 F 5 + ). Hereafter, the delay time when the pulse is turned on is determined as T .…”
Section: Experimental Methodssupporting
confidence: 54%
See 3 more Smart Citations
“…Signal time delay due to ion transit time through the QMS was considered. Our previous study 12) has confirmed the proportional relationship between the square root of ion mass number and the ion transit time, from light ions (CF + ) to heavy ions (C 3 F 5 + ). Hereafter, the delay time when the pulse is turned on is determined as T .…”
Section: Experimental Methodssupporting
confidence: 54%
“…In our previous work, 12) the ion species produced from a pulsed Ar/C 4 F 8 /O 2 plasma were Ar , and C 3 F 5 + were the dominant ions in this study. This is consistent with the calculated ionization rates based on ionization cross sections, 13) and hereafter, we focus on these five ion species.…”
Section: Experimental Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…Furthermore, plasma light intensity is linearly proportional to ion density. [25][26][27] Since the ion density at the SWP near the quartz disk is higher than that of the bulk region by more than 10 times, the light intensity would surpass that from the bulk by at least 10 times, leading to the SWP being the dominant light source for the image. In this sense, it is reasonable to think the measurement results reflect the inhomogeneous distribution of the SWP.…”
Section: Resultsmentioning
confidence: 99%